STRATEGI PENGEMBANGAN OBJEK WISATA LEMBAH HARAU OLEH DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN LIMA PULUH KOTA SEBAGAI OBJEK WISATA TAHUN 2017-2018 - Ikhlas Maulana Agus; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Harau Valley area is one of the leading tourist areas that will be developed with a priority for developing a nagari-based tourism area. With the condition of the Harau Valley Area that has not been well organized, a Regional Spatial Plan (RTRW) for the Province of West Sumatra 2012-2032 was established which became the basis for determining the Regional Regulation of the Fifty Cities Regency Number 7 of 2016 concerning the Master Plan for Tourism Development (RIPK) of the Fifty Cities Regency. 2016-2032 as a form of long-term plan for the Regency of Fifty Cities in tourism development. The basis for the formation of the 2016-2021 Regional Action Plan by DISPARPORA (Department of Youth and Sports Tourism) which is a strategy for developing the Harau Valley natural tourism area. The purpose of this study is first to describe and analyze the development strategy that has been carried out by DISPARPORA (Department of Youth and Sports Tourism) in the development strategy of the Harau Valley Nature Tourism Location and to analyze whether the strategic plan that has been set is running as planned, Second about the factors Inhibiting factors that affect the implementation of the development of the Harau Valley Tourism Object. This research method uses a qualitative approach with a descriptive type of research. The results of this study indicate that the development strategy carried out by DISPARPORA is to carry out special strategies in the natural tourist sites of the Harau Valley such as (1) Harau Valley Destination Development Strategy (2) Tourism marketing development strategy in Harau Valley (3) Tourism industry development strategy in Harau Valley ( 4) The strategy for developing tourism institutions in the Harau Valley (5) The strategy for developing the creative economy in the Harau Valley. However, the implementation has not run optimally as can be seen from strategic management, which results in several plans that do not run optimally. Keywords: DISPARPORA, Strategy, Strategic Management